Profit-driven and deman-driven investment growth and fluctuations in different accumulation regimes - Giovanni Dosi; Mauro Sodini; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2013)
The main task of this work is to develope a model able to encompass, at the same time, Keynesian, demand-driven, and Marxian, profit-driven determinants of fluctuations. Our starting point is the Goodwin's model (1967), rephrased in discrete time and extended by means of a coupled dynamics structure. The model entails the combined interaction of a demand effect, which resembles a rudimentary first approximation to an accelerator, and of a hysteresis effect in wage formation in turn affecting investments. Our model yields business cycle movements either by means of persistent harmonic oscillations, or chaotic motions. These two different dynamical paths accounting for the behaviour of the system are influenced by its (predominantly) profit-led or wage-led structures.
Keywords: E32; E11; E12; E17; 330; Endogenous Growth; Business Cycles; Investment; Aggregate Demand; Complex Systems; Nonlinear Dynamics; Chaos Theory